Clinical and epidemiological overview of liver fibrosis and hepatocellular carcinoma in patients infected with the hepatitis C virus (Research, Society and Development, 2020)
About 2.4 million people die each year worldwide as a result of chronic infection with the hepatitis C virus (HCV). HCV is a worldwide problem, more than 170 million people are infected with the virus worldwide, corresponding to about 3% of the population. Some common signs for patients chronically infected with HCV are: increased liver enzyme activity and chronic liver diseases, such as fibrosis, cirrhosis, and hepatocellular carcinoma. The present study consists of a literature review, of a qualitative nature which aims to approach the main clinical and epidemiological aspects of the chronic infection caused by the HCV. HCV detection is carried out by screening for antibodies by enzyme-linked immunosorbent assay (ELISA) and screening for HCV-RNA through polymerase chain reaction (PCR). The current detection methods are not viable for all medical centers and outpatient clinics, making it necessary to develop new detection methods, since the technological apparatus for screening HCV-RNA, as well as ELISA, is a distant reality for the vast majority of the global health system. The development of direct-acting antivirals (DAAs) increased the viral response, reaching up to 92.7% success rate. It is necessary to monitor post-treatment patients, as well as to treat patients who are still affected by the virus worldwide, to ensure that there is no progression of liver fibrosis in cirrhosis, nor the development of HCC. Additionally, vigilance should be maintained for possible mutations and the emergence of viral resistance to DAAs.